Cross-cultural adaptation and psychometric properties of the Chinese version of the Person-Centered Maternity Care Scale - Xiaoying Zhong; Rong Hu; Patience A. Afulani; Xixi Li; Xiujing Guo; Tingting He; Dehua Li; Zuowei Li (BMC Pregnancy and Childbirth, 2023)
Abstract Background Increasing evidence show that women across the world face unacceptable mistreatment during childbirth. Person-centered maternity care is fundamental and essential to quality of healthcare services. The aim of this study was to translate and determine the psychometric properties of the Person-Centered Maternity Care (PCMC) Scale among Chinese postpartum women. Methods A cross-sectional study was conducted among 1235 post-partum women in China. The cross-cultural adaptation process followed the Beaton intercultural debugging guidelines. A total of 1235 women were included to establish the psychometric properties of the PCMC. A demographic characteristics form and the PCMC were used for data collection. The psychometric properties of the PCMC were evaluated by examining item analysis, exploratory factor analysis, known-groups discriminant validity, and internal consistency. Results The number of extracted common factors was limited to three (dignity & respect, communication & autonomy, supportive care), explaining a total variance of 40.8%. Regarding internal consistency, the Cronbach’s alpha coefficient and split-half reliability of the full PCMC score were 0.989 and 0.852, respectively. Conclusions The Chinese version of the PCMC is a reliable and valid tool to assess person-centered care during childbirth in China.